INFLUENCE OF PARTICIPATION OF STUDENT COUNCILS IN CONFLICT RESOLUTION IN MANAGEMENT OF PUBLIC BOYS’ AND GIRLS’ BOARDING SECONDARY SCHOOLS, NYERI COUNTY, KENYA. - Muthui, Eustace Murage; Muthaa, George M.; Hillary, Barchok K.; Wamukuru, David K. (Machakos University, 2019)
The purpose of this study was to determine the influence of students’ council’s participation in conflict resolution on management in boys’ and girls’ public boarding secondary schools. The study adopted the descriptive survey and correlation research designs. The study was conducted in 12 boys’ and 12 girls’ public boarding secondary schools in Nyeri County that were identified using purposive sampling technique. A sample of 384 respondents was used. Data was collected using questionnaires. Data was analyzed using both descriptive and inferential statistics. The study found that participation of student council in conflicts resolution had statistically significant influence on management of public boys’ and girls’ boarding secondary schools. The study concluded that a unit increase in participation of student councils in conflict resolution enhances school management by a factor of 0.887. The study recommended that there is need to enhance guidance and counseling among students, organize forums to train student councils on conflict resolution strategies and promote moral behavior and characters in order to be trusted in resolving conflicts among students
Keywords: School management; Students Council; Conflict resolution; Secondary school